Sustainable small business lending - Sebastian Rink (Sustainable Futures)
Banks are the main source of external funding for small businesses. Thus, integrating sustainability considerations in small business lending can support global sustainability efforts. In surveying German banks, I show that banks are in the process of implementing sustainable small business lending. They put more emphasis on sustainability risks than on the transformation of the business model among small businesses. Sustainable relationship lending has some relevance in creating sustainability-related soft information, although respective hard information is preferred by banks. Banks and policymakers can use the findings to better apply sustainable small business lending to sustainability and resilience efforts.